POTENTIAL STUDY OF QUINIZARIN COMPOUNDS, ALIZARIN, AND ALIZARIN DERIVATIVES AS ORGANIC BATTERIES USING THE CYCLIC VOLTAMMETRY ANALYSES - Fadhlurrahman Tsaqif, Faruq
rhc devdopmenl of secondary hallcric began in 1990 o,1,i1h inorg;m1vha. mau:ffl\ 11, n I iCo01• LiMn:O, and LiFcPO . I lowcvcr, there i \till a 'hortagc of '\CC:Ond at 1his rime. The c drnwhnck!- include mnlerial co"'INhich tend to he cxpcn1rvc and rbcrt· " 11 tendency for low cnpRcily valucc; both lhcorcti cally and cxperimall) In add1r.1<1n.. the pn::.cncc of trnn ition mctnl!. in inorganic hMcd hancnc h. !! prnperti that arc qnrtc rmt.ic and llnmmnhk. l.i1hium -ion hancry made from'Ynlhetic orgM1coi i1an alrcmaf 1'Ye fl) thrt problem Anthrnquinonc derivative arc con'lidcrcd to ha11c a large potential valU¢ arui capncity rnngc compared to imidcs and conjugated carh<1xy l ic comp<iund1 Tim '" hci.:au'I unthrnt111inonc deri,uli\ cc; can pro<luce reduced and oxid11.t:d \ptC.1 from the uirbolt)'I group ( C -o - · C-- 0 ) they have. However, 1hc solubilit) nf rhe anthraqumone derivat1"n is poor in p<llar 'lolvcn\\ . Therefore. thi reearch aim1 u, impro..,e rhc oi ntlin11 ol compounds by i11-.cning functional group' derived from cth)'lene gl)'c:r'I The l"lri;tn '" compound 1ht11 wns yn1hc<.izcd wa!. a quini7arin compound Vi ith a product ield ptrlXntagC 1>f 52.7%. In addition, the synthesis of the funclional group modification compr11mti a.lliarin produced the compound 2-(2 ((2-hydroxy)cthoxy)cthmt) j- I -hydroxyamhraqu1nnn.c: o.rt1T a idd pcrcen1ngc of 12. 1%. The reduced and oxidi.l'ed 1talC'I of anthraqwnone cr1m.pr;und can be recorded as electrolytes in cyclic voltammctry . The clcc:Trolytt i1 a mn.tunt af tetrabutylnmmonium hexalluoro phospha1e (TBAPF,,) and an1hraqu1nonc compnu in th1'i !>tud) in dimcthylformnmide (DMF) and tetrahydrofuran (THF) :wif.,,ent!t. The re,ult.<i of tbi tud) sho" the u c of anthraquinone compounds as elcctrolyt.n ith 1H-NMR.. '·C.., lL UV·Vis. and eyehe voltammetry characieri7..ation. The ent.'I a( reduced and n:\.1tfmc:d pccies can be u:;ctl to determine the band gap energy and the diffncc bct...,e:en Hr1Mr> energ,> and LUMO energy are 2.13 cV to 2.22 cV.